Warp Recovery in Radiata Pine Lumber Using Steam Treatment - Vasco-Calle, D (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2018)
Steam treatment was used in this work to correct the observed warp in dried core-wood radiata pine (Pinus radiata) lumber that appears during the industrial drying process at high temperatures. The experimental design considered seven tests and three process variables: temperature, overload, and treatment time. The warp and moisture content before and after the treatment were measured, which allowed for assessing the efficiency of the cup recovery process of the studied thermal treatment programs. Of the analyzed types of warp (twist, bow, crook and cup), only twist was observed to be relevant to the effects of the permissible wood quality classification. The results showed that the twist recovery depends on the temperature, treatment time and overload magnitude. The best treatment results were with a steaming temperature of 100 (degrees C) and an overload of 3 (ton/m(3)) applied for 6 (h), which allowed an average recovery value of approximately 43.1%. Moreover, there was an increase in the moisture content and wood density of 10% and 3%, respectively. Finally, the post-treatment of wood with superheated steam did not show a significant improvement to the warp recovery.